Formylation reactions of N-protecting 2-Amino-4-phenyl thiazole compounds - Bicer, Abdullah; Altundas, Ramazan (Elsevier, 2023)
The Vilsmeier Haack formylation reactions of 4-phenyl-N-N'-benzoyl and 4-phenyl-N-substituted (N-sulphonyl and N-phenyl)-2-aminothiazole molecules with POCl3/DMF were studied. The Crystal (6) ((E)-N'-(5-formyl-4phenylthiazol-2-yl)-N,N-dimethylformimid amide) and crystal (14) (N-phenyl-N-(4-phenylthiazol-2-yl)formamide) molecules were obtained in the formylating reactions of N,N'-benzoyl, N-sulphonyl protecting group 4phenyl thiazole molecules. In the N-phenyl substituted thiazole compound, an aldehyde functional group is added to the amine group instead of the thiazole ring to form the N-phenyl-N-(4-phenylthiazol-2-yl)formamide molecule. All compounds have been synthesized and characterized by FT-IR, 1H NMR, 13C NMR techniques, and X-ray structure analysis. These molecules demonstrate O,S-syn conformation.
Keywords: Thiazole; Vilsmeier-haack; Formylation